2020
DOI: 10.25040/ntsh2020.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Prostate Cancer Rate and Mortality in Ukraine: Current State of Affairs

Abstract: Introduction. Prostate cancer (PC) accounts for about 12% of all malignancies in men. Over the last 10 years, there has been a significant increase in the incidence of this tumor, as evidenced by statistics. Objectives. The purpose of this study was to analyze the dynamics of PC morbidity and mortality rate in Ukraine and its regions in recent years. Materials and methods. The analysis of PC morbidity and mortality rates in Ukraine was performed in accordance with the 1999-2012 Bulletin of the National Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A meta-analysis by Yang L et al revealed that cancer is an independent risk factor for mortality in COVID-19 patients [8]. Moreover, the presence of malignancy has been identified as one of the key contributing factors impacting the mortality pattern in patients with ischemic heart disease, hypertension, and diabetes mellitus [9]. Additionally, anemia, which is commonly present in patients with bone marrow cancer, serves as risk determinant of severe COVID-19 outcomes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Yang L et al revealed that cancer is an independent risk factor for mortality in COVID-19 patients [8]. Moreover, the presence of malignancy has been identified as one of the key contributing factors impacting the mortality pattern in patients with ischemic heart disease, hypertension, and diabetes mellitus [9]. Additionally, anemia, which is commonly present in patients with bone marrow cancer, serves as risk determinant of severe COVID-19 outcomes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PC) is a malignant neoplasm that develops from the epithelium of the prostate. This disease is one of the most common cancers among men, as it ranked 4th after cancer of the trachea, bronchi, lungs, colon and rectum and stomach cancer in 2019 [1,2]. This type of cancer is most common for men over the age of 50 [2,3].…”
Section: Introductionmentioning
confidence: 99%